Evaluation Of Raw Material Procurement And Added Value Of Premium Freshwater Salted Fish Products Based On Seasonality In Tulang Bawang Regency - Abdurrokhim, Muhammad; Akbar, M. Farandika; Efendi Nasution, Erwin; Safitri, Yuli; Ari Irawan, Sahrul (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2026)
This study aims to evaluate the procurement of raw materials for freshwater salted fish based on the six-right principles and to analyze the added value of leading agroindustrial products in Tulang Bawang Regency during the dry and rainy seasons. Data were collected through a census method involving 37 business units from December 2023 to February 2024, using a descriptive quantitative approach. The results show that raw material procurement practices vary by season. In the dry season, procurement was appropriate in terms of location, quality, and price, but less accurate regarding timing, type, and quantity. In the rainy season, only location and quality criteria were consistently met. Lais fish consistently generated the highest added value, while the lowest varied between gabus and baung fish depending on the season. These findings highlight the need for adaptive, season-based strategies and call for a re-evaluation of lais fish as a flagship product due to its limited availability as an endemic species.